The Interplay Between Diet and the Epigenome in the Pathogenesis of Type-1 Diabetes - Kohil, Amira; Al-Asmakh, Maha; Al-Shafai, Mashael; Terranegra, Annalisa (Frontiers in Nutrition, 2021)
The autoimmune disease, Type 1 Diabetes Mellitus (T1DM), results in the destruction of pancreatic β-cells, and the International Diabetes Federation reports that its incidence is increasing worldwide. T1DM is a complex disease due to the interaction between genetic and environmental factors. Certain dietary patterns and nutrients are known to exert epigenetic modifications in physiological conditions and diseases. However, the interplay between diet and epigenetics is not yet well understood in the context of T1DM. Several studies elucidated the epigenetic mechanisms involved in the autoimmune reactions that destroy the β-cells, but few considered diet components as triggers for epigenetic modifications. Clarifying the link between diet and epigenome can provide new insights into the pathogenesis of T1DM, which could lead to new diagnostic and therapeutic approaches. In this mini review, we shed light on the influence of the diet-epigenome axis on the pathophysiology of T1DM.